The Mycoplasma spp. ‘Releasome’: A New Concept for a Long-Known Phenomenon - Gaurivaud, Patrice; Tardy, Florence (Frontiers in Microbiology, 2022)
The bacterial secretome counts polypeptides expressed at the cell-surface or released into the extracellular environment as well as the corresponding secretion machineries. Despite their reduced coding capacities, Mycoplasma spp. are able to produce and release several components into their environment, including polypeptides but also exopolysaccharides and extracellular vesicles. Technical difficulties in purifying these elements from the complex broth media used to grow mycoplasmas have recently been overcome by optimizing growth conditions and switching to chemically-defined culture media. However, the secretion pathways responsible for the release of these structurally varied elements are still poorly described in mycoplasmas. To clarify this issue, we propose to use the term ‘releasome’ instead of secretome to refer to molecules released by mycoplasmas in their environment. The aim of this review is to more precisely delineate the elements that should be considered part of the mycoplasmal releasome and their role in the interplay of mycoplasmas with the host cells and tissues.